In the house MTV's The Real world : Seattle - Solomon, James (New York MTV Books Pocket Books, 1998)
Wake up and smell the coffee. This is The Real World-in Seattle.

Get an insider's tour of the city of gourmet grind and alternative rock--and go behind the scenes in the Real World-Seattle cast. Off-camera and off-the-cuff, hear what Lindsay, Rebecca, Janet, Nathan, Stephen, Irene and David had to say about them. Join the Seattle Seven as they reveal the city's most happening hangouts, rock as disc-jocks at a local radio station and uncover the down-and-dirty that never made it on the air. Unrestrained and uncensored, get the how, who, what, where, when and why on The Real World-Seattle.

-How did each cast member get picked for the show?
-Who gossiped, groped and got down with whom?
-What were their lives like in the real world before The Real World (with the inside scoop on family, friends and "first times")?
-Where did they hide out from the cameras and one another?
-When, if ever, do each of the cast members hope to see each other again? And...
-Why they annoyed, enjoyed, bored and bonded with each other.
CMC-2482 donated by Ms. Triccie Cantero, U.P. Samaskom 84.1.
Keywords: Real world (Television program : United States).; Television programs -- United States; Television programs -- Casting -- United States